Distributed temperature sensor (DTS) technology for anomaly monitoring & analytics of gas pipeline - Dutta Diptarag (2018)
In Singapore, town gas is one of the major utility products which caters to the need of households in cooking and power generation. Town gas is distributed using a complex network of pipelines running beneath the ground stretching over several miles. These pipelines are mostly constructed using iron which is susceptible to wear-out and rusting. As a result, these underground Gas Distribution Networks encounter a typical problem of leakage and water ingression through the cracks or leakage points. Due to water ingression, the pipelines get blocked and the ingressed water gets spread in the distributed gas network which aggravates the problem. Moreover, the town gas is highly flammable and the leakage of this flammable gas may cause fire hazards. There are many similar incidents all over the world which are caused because of the leakage of hazardous gas. So, it is desirable and obligatory to detect and rectify any leakage at its natal stage. However, being obscured from human eyes, the early detection and localization of the cracks or leakage points in a pipeline are very difficult. Moreover, replacing these underground faulty pipes is expensive and an arduous deal. And if the exact leak location is unknown then it takes even more time and resources to dig the ground and replace the defective parts. Distributed Temperature Sensing (DTS) in the gas pipeline could provide a promising solution to this problem. When there is water ingression through cracks, the temperature at the leakage points drops. This low-temperature zones can be detected with its exact locations using DTS technology. In this thesis, we have conducted experiments (water ingression test) on a real-time experimental set up of gas pipeline using DTS system. Data analysis is carried out using two algorithms using MATLAB. The tests are conducted in two phases with above ground and underground testbed. Based on the test results, we are able to locate water ingression with an accuracy of 2m to 3m. In a practical implementation, this will help in tracing the faulty pipeline and repair the leak without digging the whole area or the entire pipeline.